Development of an Online Course Using Situated Learning and ESA Method to Enhance English Oral Communication Ability of University Administrative Staff - Matyakhan, Tatchakrit; Sukavatee, Pornpimol (An Online Journal of Education, 2021)
Since English is a medium of communication in Higher Education offered international programs, it requires university administrative staff to be able orally communicate with academic staff, international students and partner universities in English. The study aims to investigate the effectiveness of an online course using situated learning and ESA method to enhance oral communication ability of university administrative staff and perceptions towards to course. The research employed single group pre-test-post-test research design. The population of this research study was public university administrative staff in Bangkok, Thailand. In this study, the participants were 20 university administrative staff, selected by using convenience sampling technique. The findings revealed the significant increase of the staff’s oral communication ability. Moreover, they reported mainly positive perception towards the course concerning the instruction and online learning. It is concluded that the online course is beneficial to the university administrative staff according to the findings of the significant improvement and the positive perceptions.